Experiences and coping strategies during the COVID-19 pandemic among fishers and farmers in the island Province of Guimaras, Philippines - Gange, Gay Margarett A.; Eluriaga, Louie Marie T.; Ferrer, Alice Joan G. (2021)
This study describes the experiences and coping strategies related with the COVID-19 threat and the community quarantine policy by the fishers and farmers in the island province of Guimaras. Both food producers faced marketrelated problems such as low demand, low prices of catch and produce, and logistical problems. While the in-kind support (e.g., food provisions) received and adaptive measures (e.g., continued with fishing or adjusted harvest schedule; use of social media or delivery services in marketing) allowed them to get by during the pandemic, there is a need to develop more resilient farming and fishing households. Short-term support can be in the form of cash, production inputs, marketing, and credit. Long-term support can include diversifying livelihood providing savings and loan services, improving post-harvest handling and processing, including the marketing facilities, improving the modes of marketing, and promoting cooperatives.
Keywords: Farmers' attitudes; Fishers -- Social conditions; COVID-19 pandemic -- Economic aspect